2023
DOI: 10.1007/s00167-023-07611-9
|View full text |Cite|
|
Sign up to set email alerts
|

Constitutional and postoperative joint line obliquity can predict serial alignment change after opening‐wedge high tibial osteotomy: analysis using coronal plane alignment of the knee classification

Joon Hee Cho,
Hee Seung Nam,
Seong Yun Park
et al.

Abstract: Purpose The purposes of this study were (1) to clarify the distribution of the Coronal Plane Alignment of the Knee (CPAK) phenotype in patients who underwent medial opening-wedge high tibial osteotomy (OWHTO) and ( 2) to identify the predictive factors for postoperative serial alignment changes after OWHTO by analyzing constitutional phenotypes. Methods Patients who underwent OWHTO between March 2014 and December 2019 were retrospectively evaluated. Those who completed a minimum follow-up of 3 years were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In the existing literature, there are very few studies discussing that directly examine the relationship of CPAK JLO value or apex position with clinical outcomes. While the CPAK classification has become widely used in Total knee arthroplasty (TKA), its applicability in OWHTO and UKA remains unclear [2, 19]. One of the indirect findings of our study was that the use of the CPAK classification apex position in osteotomy indication and clinical follow‐up cannot provide real value and will be insufficient to evaluate radiographic findings.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In the existing literature, there are very few studies discussing that directly examine the relationship of CPAK JLO value or apex position with clinical outcomes. While the CPAK classification has become widely used in Total knee arthroplasty (TKA), its applicability in OWHTO and UKA remains unclear [2, 19]. One of the indirect findings of our study was that the use of the CPAK classification apex position in osteotomy indication and clinical follow‐up cannot provide real value and will be insufficient to evaluate radiographic findings.…”
Section: Discussionmentioning
confidence: 88%
“…Precise measurement of KJLO is a key factor, especially in osteotomy surgeries [2,22,25]. OWHTO alone can cause abnormal changes in KJLO, but double-level osteotomy may eliminate this risk [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, complex biomechanics may have contributed to the statistical significance. Many recent studies on JLO associated with HTO have been reported [38–41]; however, most covered the association between postoperative JLO and clinical outcomes. The association between preJLO and ∆JLCA seems to be an area that requires further study.…”
Section: Discussionmentioning
confidence: 99%